2000
DOI: 10.2746/042516400777591660
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxytocin on contractility of the equine oesophagus: a potential treatment for oesophageal obstruction

Abstract: Summary This study was performed to determine the effect of administration of i.v. oxytocin on the contractility of the musculature associated with the equine oesophagus. Nine clinically normal horses were fitted with a nasogastric tube modified with inflatable latex cuffs. These cuffs were connected to piezoelectric pressure recording devices. Oxytocin in 3 different doses or saline controls were administered i.v. in a randomised block pattern. Systolic blood pressure, ECG, heart rate and nasogastric tube cuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
0
16
0
2
Order By: Relevance
“…In the study by Meyer et al . () several doses of i.v. oxytocin were shown to cause intramural pressure reduction due to relaxation of the striated muscle located in the proximal two‐thirds of the oesophagus.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Meyer et al . () several doses of i.v. oxytocin were shown to cause intramural pressure reduction due to relaxation of the striated muscle located in the proximal two‐thirds of the oesophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin (0.11-0.22 IU/kg IV) has been reported to induce transient relaxation of esophageal musculature in healthy horses and resolution of choke in 8 of 10 horses. 13 However, other investigators have not been able to corroborate these findings using manometric evaluations of the esophagus in the absence of balloon distention of the esophagus.…”
Section: Discussionmentioning
confidence: 97%
“…However, other studies have demonstrated some effect on contractility as measured by piezoelectric pressure transducer (Meyer et al . ). In this study, the placement of the transducer induced internal pressure on the oesophagus and then measured the oesophageal resistance to that pressure after the administration of oxytocin.…”
Section: Further Commentary Oesophageal Relaxationmentioning
confidence: 97%